Quality of live and migration expectations of young people of rural in the State of Mexico - Mercado-Salgado, Patricia (2013)
Background. It seems that inequality is the goal, and now more than ever young people is affected by it; educational backwardness, lack of decent jobs and the consequent financial needs are fundamental reasons to accept migration as individual and family strategy to improve living conditions. Objective. Describe the quality of life and expectations of U.S. migration of young rural northeastern Mexico State. Materials and method.Quantitative and descriptive study; a probabilistic sample of 496 rural young people; a questionnaire was applied. We hypothesize a relationship between perceived quality of life and migration expectations. Results. By describing quality of life of rural youth people, eight dimensions have opportunities for improvement. The best qualified are physical component and the development of daily activities. More urgent to address are expectations of development (including employment) and environment (including security). Conclusions. By improving the quality of life of rural youth population, their migration expectations would be lower and would increase equality between men and women. To reduce migration, our country cannot depend on the United States economic conditions. It's urgent to improve the quality of life in the ejector communities.